Indicators for preventable drug related morbidity: application in primary care. Issue 3 (2nd June 2004) - Morris, C J; Rodgers, S; Hammersley, V S; Avery, A J; Cantrill, J A
Abstract : Aim: To apply in practice a series of validated indicators for preventable drug related morbidity (PDRM). Design: A pilot study to identify retrospectively potential PDRM events over a 2 year 3 month time frame using the MIQUEST computer software program. Subjects and setting: The electronic patient record of all patients aged 18 years and over in nine English general practices. Outcome measures: The number of potential PDRM events identified, as defined by the indicators. Results: Five hundred and seven potential PDRM events were identified from 49 658 electronic patient records, giving an overall incidence of 1.0%. A small number of the indicators (n = 4) accounted for approximately 60% of the events, while for many indicators few events were identified. The most common events related to the use of non-steroidal anti-inflammatory drugs in patients with congestive heart failure or hypertension, lack of monitoring in patients prescribed angiotensin converting enzyme inhibitors, and the use of hypnotic-anxiolytic agents. Conclusions: A small number of indicators contributed to the majority of the PDRM events. Interrogation of electronic patient records in primary care using computerised queries shows potential for detecting PDRM.